2018
DOI: 10.4236/ojbiphy.2018.83012
|View full text |Cite
|
Sign up to set email alerts
|

Specific Radius Change of Quantum Dot inside the Lipid Bilayer by Charge Effect of Lipid Head-Group

Abstract: We studied the quantum dot-liposome complex (QLC), which is the giant unilamellar vesicle with quantum dots (QDs) incorporated in its lipid bilayer. A spin coating method in conjunction with the electroformation technique yielded vesicles with highly homogeneous unilamellar structure. We observed QD size dependence of the QLC formation: QLCs form with blue, green and yellow-emission QD (core radius ~1.05 nm, 1.25 nm and 1.65 nm) but not with red-emission QD (core radius ~2.5 nm). In order to explain this size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…For one, it has been widely reported that quantum dot-lipid systems will adopt one of two morphologies depending on the characteristic nanoparticle size D QD and the membrane elastic interface energy change Δ E def associated with membrane “wrapping” about the particles – a quantum dot-micelle complex (QMC) or a quantum dot-liposome complex (QLC). 18,36,37 QLCs consist of nanoparticles embedded fully within a lipid bilayer, whereas QMCs are the reverse configuration – lipid bilayers fully covering an interior of single (or multiple) QDs. When the QD size distribution straddles a certain critical size D crit , corresponding to the point where Δ E def is equal for both QLC and QMC states, one would expect to observe both QLC and QMC structures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For one, it has been widely reported that quantum dot-lipid systems will adopt one of two morphologies depending on the characteristic nanoparticle size D QD and the membrane elastic interface energy change Δ E def associated with membrane “wrapping” about the particles – a quantum dot-micelle complex (QMC) or a quantum dot-liposome complex (QLC). 18,36,37 QLCs consist of nanoparticles embedded fully within a lipid bilayer, whereas QMCs are the reverse configuration – lipid bilayers fully covering an interior of single (or multiple) QDs. When the QD size distribution straddles a certain critical size D crit , corresponding to the point where Δ E def is equal for both QLC and QMC states, one would expect to observe both QLC and QMC structures.…”
Section: Resultsmentioning
confidence: 99%
“…When the QD size distribution straddles a certain critical size D crit , corresponding to the point where Δ E def is equal for both QLC and QMC states, one would expect to observe both QLC and QMC structures. 18,37 QMC structures in particular are manifested in optical microscopy by small, bright lipid-QD aggregates. 18 The critical D crit for the 18-acyl-carbon unsaturated lipid 1,2-dioleoyl- sn-glycero -3-phosphocholine (DOPC) was previously reported as approximately 6.5 nm; 18 if we assume DPPC (16 acyl-carbon) has a similar D crit , then it might be reasonable to expect the formation of some CdSe QMCs and some QLCs, since our CdSe-520 has a TEM-verified size of approximately 6 nm including ligands.…”
Section: Resultsmentioning
confidence: 99%